A Review of Bed Nets Usage and Sewerage Conditions as Risk Factors for Lymphatic Filariasis in Developing Countries - Azzahra, Muhafasya Karunia; Shafwah, Diva Alishya; Sondakh, Cresti Sukmadevi; Retno Adriyani (Universitas Airlangga, 2024)
Introduction: Lymphatic filariasis, a neglected tropical disease (NTD), is a parasitic disease caused by microscopic worms that live only in the human lymphatic system. Mosquitoes, as vectors of lymphatic filariasis, play an important role in the prevention of this disease. The aim of this study was to identify agent, vector, and physical environment risk factors for filariasis in developing countries through a literature review. Discussion: This study was conducted using the narrative literature review method. The main sources for this study were articles from Google Scholar, Research Gate, PubMed, Springer, Scopus, and DOAJ databases. The criteria for articles were published between 2012 and 2022, observational studies including cross-sectional, case-control, and cohort designs, open access, and articles were organized according to STROBE guidelines. This study showed that from a total of 100 articles found, 14 articles met the predetermined criteria. Wuchereria bancrofti is the most common agent of filariasis. Culex and Anopheles are the vectors. The presence of bed nets and sewerage conditions were physical environment risk factors for filariasis in developing countries. Conclusion: Prevention of filariasis can be achieved by using mosquito nets or insect repellent when sleeping at night. In addition, open drains should be cleaned regularly to prevent them from becoming breeding sites for mosquitoes as vectors.